2002
DOI: 10.1136/vr.150.23.707
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of dairy cows in Northern Ireland

Abstract: A comprehensive database was established on the milk production and reproductive performance of dairy cows in 19 selected herds in Northern Ireland, varying in size, management system and genetic merit. Data were obtained for 2471 cows, 1775 of which calved in a second year, and 693 were culled from the herd for specific reasons. The estimated mean rate of heat detection (assessed by the interheat interval during the main breeding season) in all the herds was 71 per cent, with a range from 53 to 92 per cent Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 15 publications
(26 reference statements)
5
29
1
Order By: Relevance
“…The decline in reproductive performance of the dairy herd has been widely reported with various studies around the world citing conception rates to first insemination of approximately 40% (Butler, 1998;Royal et al, 2000;Mayne et al, 2002), though this figure tends to be higher in grassbased production systems Grosshans et al, 1997). At herd level, decreased individual cow fertility, with more services per conception, has been reported in cows producing more than the herd average (Wicks and Leaver, 2004) but Darwash et al (1997) found no such phenotypic effects of yield on fertility.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The decline in reproductive performance of the dairy herd has been widely reported with various studies around the world citing conception rates to first insemination of approximately 40% (Butler, 1998;Royal et al, 2000;Mayne et al, 2002), though this figure tends to be higher in grassbased production systems Grosshans et al, 1997). At herd level, decreased individual cow fertility, with more services per conception, has been reported in cows producing more than the herd average (Wicks and Leaver, 2004) but Darwash et al (1997) found no such phenotypic effects of yield on fertility.…”
Section: Introductionmentioning
confidence: 95%
“…Herds were identified by local DARD advisers as having a good track record of data recording, a willingness and enthusiasm to participate in the study and being geographically spread throughout Northern Ireland. Twenty herds were selected as representative of those throughout the region and included a wide range of herd size, concentrate input, feeding methods, genetic merit and level of milk production, details of which are provided in Mayne et al (2002). One of these herds was later omitted from the study due to farmer illness and not replaced.…”
Section: Selection Of Participating Herdsmentioning
confidence: 99%
See 3 more Smart Citations